Clinical problems in children and youth - Martin, Grant L. (Dallas, TX Word, 1992)
Includes bibliographical references and index.
Keywords: Youth -- behavoural problems -- pastoral counselling of; Children -- behavoural problems -- pastoral counselling of; Children -- sexual abuse -- pastoral counselling of; Youth -- sexual abuse -- pastoral counselling of; Church work with youth; Church work with children